Single cell analysis of short-term dry eye induced changes in cornea immune cell populations - Alam, Jehan; Yaman, Ebru; Silva, Gerda Cristal Villalba; Chen, Rui; de Paiva, Cintia S.; Stepp, Mary Ann; Pflugfelder, Stephen C. (Frontiers in Medicine, 2024)
Background: Dry eye causes corneal inflammation, epitheliopathy and sensorineural changes. This study evaluates the hypothesis that dry eye alters the percentages and transcriptional profiles of immune cell populations in the cornea. Methods: Desiccating stress (DS) induced dry eye was created by pharmacologic suppression of tear secretion and exposure to drafty low humidity environment. Expression profiling of corneal immune cells was performed by single-cell RNA sequencing (scRNA-seq). Cell differentiation trajectories and cell fate were modeled through RNA velocity analysis. Confocal microscopy was used to immunodetect corneal immune cells. Irritation response to topical neurostimulants was assessed. Results: Twelve corneal immune cell populations based on their transcriptional profiles were identified at baseline and consist of monocytes, resident (rMP) and MMP12/13 high macrophages, dendritic cells (cDC2), neutrophils, mast cells, pre T/B cells, and innate (DT, ILC2, NK) and conventional T and B lymphocytes. T cells and resident macrophages (rMP) were the largest populations in the normal cornea comprising 18.6 and 18.2 percent, respectively. rMP increased to 55.2% of cells after 5 days of DS. Significant changes in expression of 1365 genes (adj P < 0.0001) were noted in rMP with increases in cytokines and chemokines (Tnf, Cxcl1, Ccl12, Il1rn), inflammatory markers (Vcam, Adam17, Junb), the TAM receptor (Mertk), and decreases in complement and MHCII genes. A differentiation trajectory from monocytes to terminal state rMP was found. Phagocytosis, C-type lectin receptor signaling, NF-kappa B signaling and Toll-like receptor signaling were among the pathways with enhanced activity in these cells. The percentage of MRC1+ rMPs increased in the cornea and they were observed in the basal epithelium adjacent to epithelial nerve plexus. Concentration of the chemokine CXCL1 increased in the cornea and it heightened irritation/pain responses to topically applied hypertonic saline. Conclusions: These findings indicate that DS recruits monocytes that differentiate to macrophages with increased expression of inflammation associated genes. The proximity of these macrophages to cornea nerves and their expression of neurosensitizers suggests they contribute to the corneal sensorineural changes in dry eye.